Manfaat Buku Komik terhadap Respon Maladaptif Anak Sebelum Operasi - Rehana Rehana; Eva Oktaviani; Jawiah Jawiah; Eva Susanti (Journal of Telenursing (JOTING), 2023)
This research aims to identify the benefits of comic books as an educational medium for children's physiological and psychological maladaptive responses before surgery. The method used in this research is a descriptive research method with a case study approach. The study results show that perioperative use of comic book educational media can reduce children's physiological and psychological maladaptive responses before surgery. There was a decrease in preoperative anxiety based on APAIS scores in both research subjects, namely from high stress to mild anxiety after reading perioperative comic books. In conclusion, using perioperative comic book educational media can reduce maladaptive responses in children before surgery. Keywords: Comic Book, Anxiety, Surgery, Perioperative, Maladaptive Response